La construcción de la democracia en América Latina y sus desafíos actuales - Mora Chinchilla, Carolina (2016)
This session gives an overview of the history of the Latin American political life from the various processes of independence during the second decade of the 19th century. The overall objective is to recognize the important role played by the democratic model as a decisive factor in the political development of this region and how difficult the democratic progress has been due to the economic, social, and political circumstances of Latin America. There is an analysis of the various stages of the political-electoral life of the region, which presents great contrasts that have made it difficult for democracy to succeed, a model proposed by almost all the countries since their first years of independence. Finally, it is concluded that the 1980s presents a good opportunity for the regularization of the electoral activity and the end of totalitarian governments in Latin America, even though the current challenges on regional democracy are still difficult to overcome.